2017
DOI: 10.21608/jacb.2017.38779
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Evaluation of some Rhizobacteria Isolated from Egyptian Soils, In vitro as Biofertilizers.

Abstract: Nitrogen (N), Phosphorus (P) and Potassium (K) are the major essential macro-nutrients for plants. The ability of soil bacteria to provide available forms of these nutrients to plants is an important feature in the bacterial strain used as a biofertilizer. In this study, fifteen isolates of Azotobacter spp were isolated. The efficiency levels of the N 2 -fixation were tested, the isolates reduced acetylene at rates of 6.348 -1381.023 nmoles C 2 H 4 /ml/day. The most active isolate was No. AZ 8 that identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…This may because of a consequent oxidation of organic acids created in culture media and/or to the development of natural materials at the expense of organic acids formerly made. The gotten outcomes are in agreement with those of Hauka et al (2017) and Walpola et al (2014). Table (3) showed the variations in water-soluble phosphorus values as affected by the activity of PSB on tricalcium phosphate.…”
Section: Isolation and Efficiency Of Phosphate-solubilizing Bacteriasupporting
confidence: 90%
See 1 more Smart Citation
“…This may because of a consequent oxidation of organic acids created in culture media and/or to the development of natural materials at the expense of organic acids formerly made. The gotten outcomes are in agreement with those of Hauka et al (2017) and Walpola et al (2014). Table (3) showed the variations in water-soluble phosphorus values as affected by the activity of PSB on tricalcium phosphate.…”
Section: Isolation and Efficiency Of Phosphate-solubilizing Bacteriasupporting
confidence: 90%
“…The diminution in P content with the advance of incubation period could be due to the consumption of P causing the changeable levels of P discharge, accessibility of soluble phosphorus in the culture medium might also has an inhibitory effect on further phosphate solubilization, excretory toxic yields may also responsible for such weakening in P-solubilization. The existing outcomes are matched with that of Hemalatha et al (2013), Walpola et al (2014) and Hauka et al (2017). The maximum amount of liberated phosphorus in actively developing culture was verified by isolate PSB 5 which was used as PSB inoculant in further experiments.…”
Section: Isolation and Efficiency Of Phosphate-solubilizing Bacteriasupporting
confidence: 70%
“…The results showed that A. chrococcum reached its maximum activity after 28 days of incubation, whereas B. circulans reached the maximum activity after 14 days of incubation, then was decreased. The decrease in P content with the advance of the incubation period could be attributed to the utilization of P resulting in the fluctuating levels of P release, and availability of soluble P in the culture medium might also have an inhibitory effect on further P solubilization [57][58][59][60]. Excretory toxic products may also responsible for such decline in P solubilization.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there was a rapid decrease in pH values within the first three days of the experiment, reflecting the high activity of organic carbon degradation bacteria leading to organic acids releasing which mainly contribute to the increasing pH value. The increase in pH might be due to a subsequent oxidation of organic acids produced in the culture media or might be due to the formation of other natural substances [57][58][59]. Moreover, both bacterial strains can effectively produce IAA which may contribute to improving the nutrition of maize plants.…”
Section: Discussionmentioning
confidence: 99%
“…Azotobacter chroococcum MF135558 (N2-fixing bacteria), Klebsiella oxytoca MF135559 (P-solubilizing bacteria) and Rhizobium pusense MF135560 (K-releasing bacteria) were isolated and identified by Hauka et al, (2017). Experimental design A field experiment was carried out in Fac.…”
Section: Bacterial Strainsmentioning
confidence: 99%